Hydrogen-tetrahydrofuran mixed hydrates: A computational study. (18th October 2018) - Kaur, Surinder Pal; Ramachandran, C.N.
Abstract: The present work examines the host-guest interactions in H2 -THF mixed hydrates in a fused dodeca-hexakaidecahedral cage at the molecular level. The host-guest interaction energies are analyzed to get insight on the occupancies of H2 and THF in different host cages. The maximum and optimum storage capacity of H2 in dodecahedral and hexakaidecahedral cages is determined. The studies show that THF in a hexakaidecahedral cage interacts with water molecules of the neighboring dodecahedral cage whereas H2 due to its smaller size does not interact with water molecules of a neighboring cage. The interaction energy and free energy associated with the encapsulation of guest species revealed that simultaneous encapsulation of H2 and THF in the large cavities of sII hydrates is feasible. Energy decomposition analysis indicates that electrostatic and dispersion interactions contribute significantly to the stability of the complexes. The occupancy of H2 in small and large cages of mixed hydrates are analyzed in terms of 1 H and 13 C chemical shifts. Graphical abstract: Highlights: Host-guest interactions are studied in H2 -THF mixed hydrates. The interaction of THF with water molecules of an adjacent cage is examined. Simultaneous occupancy of H2 and THF in the hexakaidecahedral cage.